The influence of carbon-glass/epoxy hybrid composite under mode I fatigue loading: Hybrid fiber bridging zone model - Monticeli, Francisco Maciel [UNESP] (2022)
A mechanistic model for mode I fatigue delamination growth based on the hybrid fiber bridging zone was developed and is described herein. The model is based on the microfracture mechanisms of striation, fiber peel-off and fiber bridging stress, measured through scanning electron microscopy analysis. The effects of the carbon and glass fiber delamination features at the microscopic level were also considered to predict the crack propagation behavior in a hybrid laminate. The experimental SERR based on the fiber bridging zone model was used as the similitude parameter for the crack growth rate, following power law.